Fake Indian Currency Recognition Using CNN and Mobile Net Algorithm - S Vinay Kumar,; S Muni Kumar, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The rise of counterfeit currency is a serious threat to our economic stability, which is why we need smarter ways to detect it. This project, called "Identification of Fake Indian Currency Using Convolutional Neural Network and MobileNet Algorithm," introduces an innovative method for spotting counterfeit notes by using deep learning techniques. The research focuses on the MobileNet model to differentiate between real Indian currencies and fakes. MobileNet is well-regarded for its efficiency and accuracy in image classification, and here, we put it to the test for identifying counterfeit money. The model is fine-tuned for both speed and precision, making it a great fit for real-time applications in counterfeit detection systems.
Keywords: Counterfeit Detection; Convolutional Neural Networks; MobileNet; Indian Currency; Image Classification; Machine Learning